Is There a Replication Crisis in Finance? - JENSEN, THEIS INGERSLEV; KELLY, BRYAN; PEDERSEN, LASSE HEJE (Journal of Finance, 2023)
ABSTRACT Several papers argue that financial economics faces a replication crisis because the majority of studies cannot be replicated or are the result of multiple testing of too many factors. We develop and estimate a Bayesian model of factor replication that leads to different conclusions. The majority of asset pricing factors (i) can be replicated; (ii) can be clustered into 13 themes, the majority of which are significant parts of the tangency portfolio; (iii) work out‐of‐sample in a new large data set covering 93 countries; and (iv) have evidence that is strengthened (not weakened) by the large number of observed factors.